Entrelaçamento da oralidade e da escrita em textos narrativos e argumentativos de estudantes do sétimo ano do ensino fundamental - Oliveira, Simone Simões (2015)
This research has as its theme the relationship between orality and writing that are established for the production of texts written narrative genres and argumentative students from the seventh grade of elementary school. The objectives are set as part of the verification on how the seventh grade students write as they speak and the study of what factors contribute for this to occur, by comparing opinion texts and legendary texts. This research is justified because it is not enough to observe how students write how they speak. In addition, the comprehension that the textual context of production contributes to occur more or less orality interference in writing can provide guidance to a Portuguese teacher to contribute with their students in acquiring proper knowledge to multiple oral textual productions and written . The theoretical framework comprises since the concepts of genres to the teaching issues of mother tongue, based mainly on studies of Charaudeau (2004, 2007, 2012a, 2012b), with regard to the organization of modes of discourse, Bahktin (1997, 1998, 2003) on the approach to gender, Bortoni- Ricardo (2004, 2005, 2008) on the sociolinguistic parameters that explain the links between oral and written, Ilari and Basso (2006), Marcuschi (2005, 2010), about the mother tongue education in Brazil. Regarding the methodology, it is a descriptive, bibliographical and qualitative research, with field research conducted in a public school in the area covered by the 36th Regional Coordination of Education, located on the periphery of the city of Ijuí / RS. The research corpus comprises legendary narrative and argumentative opinion texts produced by students of the seventh grade of elementary school. The study shows that, both the production of narrative texts (legendary), as in the production of argumentative texts (opinionated), there is interference of orality in writing. These textual productions are conditioned to the situational context in where they are expressed, which involves progression of education of students, the social environment in which they live, cognitive ability and school contributions in learning the mother tongue. Keywords: Language, text, speech, orality, writing